The The Implementation of Samapta Patrol as a Preventive Strategy in Addressing Theft Crimes in the Palembang City Police Area - Bhayangkara, Ikhlasul Amal; Suheriyadi, Bambang; Thalib, Prawitra (Dinasti Research, 2025)
The Samapta Patrol is a policing activity focused on preventive actions to reduce crime rates and ensure public security and order (Harkamtibmas). This study aims to analyze the implementation of the Samapta Patrol as a preventive strategy in addressing theft crimes within the jurisdiction of the Palembang City Police (Polrestabes Palembang). The research employs a socio-juridical method with a qualitative approach. The data sources consist of primary data obtained from interviews with Samapta Police officers and limited field observations; secondary data including laws and regulations, official police reports, and academic literature; and tertiary data comprising online articles, crime news, and statistical reports. The findings reveal that the Samapta Patrol plays a crucial role in reducing theft cases through routine patrols, dialogic patrols, and cooperation with local communities. However, its implementation still faces challenges such as limited human resources, insufficient facilities, and low community participation. In conclusion, the effectiveness of the Samapta Patrol can be enhanced through data-driven patrol planning, personnel capacity development, adequate budget allocation, and active collaboration with the community to achieve sustainable public security and order in Palembang City.